Τα «Βασιλικά Ινστιτούτα» (1706). Ένα αθησαύριστο έργο του Νικολάου Κομνηνού Παπαδοπούλου και η διάδοσή του στον ελληνικό χώρο - Τάνταλος Μάριος Θ. (The Gleaner, 2011)
THE «ROYAL INSTITUTES» (1706) An Unknown Work of Nikolaos Komnenos Papadopoulos and its Diffusion Three 18th-century manuscripts – Patmiacus gr. 361, Metochion [monastery dependency] of the Holy Sepulchre of Constantinople 449 and Greek Philological Society of Constantinople [Türk Tarih Kurumu] 59 – undoubtedly contain the same unpublished text, namely the «Royal Institutes». The «Royal Institutes» is a didactical explanation in Greek of the Justinian «Institutes». In this paper, we propose that its author was Nikolaos Komnenos Papadopoulos, a Cretan professor at the law school of Padua. We also argue that Papadopoulos completed the «Royal Institutes» in the spring of 1706, as requested by his former student and later the Patriarch of Jerusalem, Chrysanthos Notaras. Chrysanthos, in turn, used the «Royal Institutes» as a source for his own compendium, the «Introduction to the Laws». MARIOS TANTALOS